Physiological and molecular mechanisms of exogenous salicylic acid in enhancing salt tolerance in tobacco seedlings by regulating antioxidant defence system and gene expression - Song, Xiliang; Chen, Jian; Xu, Can; Cai, Xianjie; Song, Wenjing; Chang, Aixia; Zhang, Yu; Luo, Chenggang (Frontiers in Plant Science, 2025)
IntroductionSalt stress has emerged as a predominant abiotic factor that jeopardizes global crop growth and yield. The plant hormone salicylic acid (SA) has notable potential in mitigating salt toxicity, yet its mechanism in enhancing the salinity tolerance of tobacco plants is not well explored.MethodsThis study aimed to assess the potential benefits of exogenous SA application (1.0 mM) on tobacco seedlings subjected to saline soil conditions.ResultsThe foliar spray of SA partially mitigated these salt-induced effects, as evidenced by a reduction of malondialdehyde content, and improvements of leaf K+/Na+ ratios, pigment biosynthesis, and electron transport efficiency under NaCl stress. Additionally, SA increased the contents of total phenolic compound and soluble protein by 16.2% and 28.7% to alleviate NaCl-induced oxidative damage. Under salt stressed conditions, the activities of antioxidant enzymes, including superoxide dismutase, ascorbate peroxidase, catalase, and peroxidase increased by 4.2%~14.4% in SA sprayed tobacco seedlings. Exogenous SA also increased ascorbate and glutathione levels and reduced their reduced forms by increasing the activities of glutathione reductase, ascorbate peroxidase, monodehydroascorbate reductase and dehydroascorbate reductase. qRT−PCR analysis revealed that the key genes regulating SA biosynthesis, carbon assimilation, the antioxidant system and the ascorbate−glutathione cycle were activated by SA under conditions of salt stress.DiscussionOur study elucidates the physiological and molecular mechanisms of exogenous SA in enhancing plant salt tolerance and provides a practical basis for crop improvement in saline environments.